Using Dictation to Promote the Use of Grammar Knowledge in Reconstructing Listening Texts - Hesthi Herusatoto (Celt: A Journal of Culture, English Language Teaching & Literature, 2016)
This paper reports the findings of the implementation of full dictation and partial dictation in improving the awareness of using grammar knowledge in reconstructing listening texts among the EFL students at STBA (School of Foreign Languages) LIA Yogyakarta. Three groups participated in the study, i.e. two experimental groups (Group A and B) and a control group (Group C). A pre-test on listening to lectures was administered to the three groups. Over 9 sessions, Group C did the listening exercises in their textbook using dicto-comp technique, while in addition to the listening exercises which applied dicto-comp, the students in Group A was given full dictation exercises and Group B received partial dictation exercises. A post-test was given to the three groups after the ninth session. In addition to the post-test, a 5-point Likert-scale questionnaire assessing the students responses to the dictation exercises was given to the experimental groups. Results of paired-samples tests indicated that there was a significant difference between each groups pre- and post-test. The mean gain score of Group B was higher than Group A showing that Group B had better improvement in the post-test. Furthermore, Group B had better grammar points in their post-test compared to Group A. Group C also increased their scores but they still got their teachers assistance to point out their grammatical mistakes in their notes. This suggests that the dictations given to the experimental groups improved the students awareness in applying their grammar knowledge to reproduce a listening text they heard.